Learning, playing, and experimenting with critical food futures - McGreevy, Steven R.; Rupprecht, Christoph D. D.; Tamura, Norie; Ota, Kazuhiko; Kobayashi, Mai; Spiegelberg, Maximilian (Frontiers in Sustainable Food Systems, 2022)
Imagining sustainable food futures is key to effectively transforming food systems. Yet even transdisciplinary approaches struggle to open up complex and highly segregated food policy governance for co-production and can fail to critically interrogate assumptions, worldviews, and values. In this Perspective we argue that transdisciplinary processes concerned with sustainable food system transformation need to meaningufully engage with critical food futures, and can do so through the use of soft scenario methods to learn about, play with, and experiment in futures. Specifically, soft scenarios contribute in four ways: 1) questioning widely held assumptions about the future; 2) being inclusive to multiple perspectives and worldviews; 3) fostering receptiveness to unimaginable futures; 4) developing futures literacy. Based on insights from a 5-year transdisciplinary action research project on sustainable food transformation across Asia, we demonstrate how these processes play out in narratives, serious games and interactive art featuring soft scenarios. We conclude by discussing the potential for collaboration between transdisciplinary and futures researchers, especially for transforming food systems.